Evaluation of Information Dissemination on Disaster Preparedness of Barangay Public Safety Officer in Barangay Novaliches Proper Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A disaster is a major issue that affects a community or society for an extended period of timeand results in widespread loss of people, property, economic resources, or the environment.The character of people who have experienced disasters frequently in the environment tendto think that disasters are a normal occurrence and feel like they already know everything, sothey are passive in seeking disaster information. Hence, this study aimed to evaluate theinformation dissemination on disaster Preparedness of Barangay Public Safety officers inNovaliches Proper Quezon City.The main purpose of this is to formulate a proposed program that may help theadministration to ensure safety and security when it comes to disaster preparedness. Thestudy proposed a disaster theory about the Crunch and Release model, which indicates whythe disaster occurs and how it can be avoided or reduced. The study revealed that themajority of the respondents encountered more challenges in disaster response vehicles,tents, and other temporary shelters and facilities for evacuation centers. While most of theresidents are not participating when it comes to evacuation and program for disaster drillsand also the data gathered, it is concluded that Barangay Novaliches Proper was needed toconduct a hazard map inspection and maintenance. The study suggested that the Barangayofficial may provide a recommendation letter to the local government to ask for help withtheir budget and expenses regarding vehicles and other facilities such as tents forevacuation. Also, keep the community well prepared by disseminating knowledge on how tobe prepared when disaster happens. Residents can participate by attending seminars,programs, and training to raise disaster risk awareness and preparedness. Finally, the studysuggested that BPSO conduct a further study that focuses on developing other materialsand standard procedures like Fire, Earthquake, Typhoon, and Flood Drills.To better respond to and manage the immediate aftermath of a disaster, whether it ishuman-induced or brought on by natural hazards, communities or individuals take a numberof precautions in advance.
Keywords: Business Administration